Saudi Arabia in the Anglo-American press - Alrebh, Abdullah, author.
1 online resource.
Keywords: "This book provides an in-depth analysis of authority structures in Saudi Arabia during the twentieth century, as presented in two leading Western newspapers, The London Times and The New York Times. Beginning with a history of Saudi Arabia - from the building of the Kingdom in 1901, when Ibn Saud left his exile in Kuwait to recover Riyadh back from Al-Rasheed's rule, until the death of King Fahd in 2005 - the author then outlines the theoretical framework of the book, specifically Weber's original conception of authority. Weber's notion of authority as having three types - traditional, charismatic, and rational-legal - is applied to an analysis of the two newspapers over the course of the twentieth century. A timeline is devised to aid this analysis, based on significant turning points in Saudi history, including Ibn Saud's declaration of the Kingdom in 1932 and King Faisal's assassination in 1975. Ultimately, this analysis discloses the many ways in which conceptions of authority in the Middle East were presented to Western audiences, whilst illuminating the political agendas inherent to this coverage in the UK and the US. This book is vital reading for anyone interested in Saudi Arabian history, Western perspectives of the Middle East, and the sociology of media"--